Implementation of Experiential Marketing in an Effort to Increase Tourists' Visiting Decisions at the Cimincul Springs Camping Ground Tourist Attraction, Subang Regency - Novianto, Untung; Bahri, Khoirun Nisa; Jannah, Siti Alif Betha Nur (SEAN Institute, 2024)
The aim of this research is to find out how the implementation of Experiential marketing can improve tourists' visiting decisions. The method used in this research uses a qualitative method. The respondents used in this research were 4 tourists and managers using random sampling. The government's plan, based on the strategic plan of the Ministry of Tourism and Creative Economy, initiates how to revive the tourism sector after the Covid-19 pandemic and revive the community's economy through the tourism sector. The Ministry of Tourism and Creative Economy has a strategy to develop a tourist destination that prioritizes positive value for tourists, so that it can contribute to exploring existing potential. in their respective places or explore their own potential which can be collaborated with this tourism sector. One of them is the establishment of a Camping Ground, which is how the management can provide a positive experience for tourists. After this Camping Ground became increasingly well known and had a positive image, indirectly the management and the community could directly enjoy the results. Based on the description above, research was conducted regarding the Implementation of Experiential Marketing in an Effort to Increase Tourists' Visiting Decisions at the Cimincul Springs Camping Ground Tourist Attraction, Subang Regency. The method used in this research is qualitative, with interview, observation and documentation methods. The number of resource persons in this research was 4 resource persons consisting of management and tourists at the Mata Air Cimincul Camping Ground. The results of this research show that the implementation of Experiential Marketing has contributed to increasing tourists' visiting decisions, with more and more tourists visiting the Cimincul Subang Springs Camping Ground.